Metabolite Profiling of The Antioxidant Properties of The Aquatic Plant Cyperus involucratus Employing UHPLC-HRMS - Ari Sri Windyaswari; Fahrauk Faramayuda; Salsa Rizqyana Billa; Maria Tri Miarsih; Inna Puspa Ayu; Niken Tunjung Murti Pratiwi; Majariana Krisanti; Fifi Gus Dwiyanti (Universitas Lambung Mangkurat, 2026)
The genus Cyperus is widely recognized as decorative flora. Empirically, Cyperus plants have been utilized to treat wounds, inflammation, and digestive disorders. While the genus is reported to exhibit antioxidant properties, scientific data regarding Cyperus involucratus remains limited. This research aimed to identify antioxidant compounds in C. involucratus using Ultra-High-Performance Liquid Chromatography-High Resolution Mass Spectrometry (UHPLC-HRMS). The C. involucratus methanolic extract was obtained through maceration using a 70% methanol solvent. Separation was performed using a UHPLC gradient system with a flow rate of 0.3 mL/min , while compound identification was conducted using a Quadrupole-Orbitrap MS detector in positive mode. The radical scavenging activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. The analysis identified 175 metabolites within the methanolic extract. Based on mzCloud library matching with confidence scores of 97.4–100%, 12 primary bioactive compounds were identified: oleamide, α -linolenic acid, kaempferol, scutellarin, hexadecanamide, 1-linoleoyl glycerol, 1-stearoy-rac-lglycerol, adenine, adenosine, L-tyrosine, stearamide and nootkatone. The extract possessed a moderate radical scavenger with an IC50 value of 57.94 μg/mL. These findings provide a scientific foundation for further investigation of C. involucratus as a potential natural antioxidant, although further in vivo studies are required to validate its broader pharmacological outcomes.